MICROFINANCE AND WOMEN'S ENTREPRENEURIAL SUCCESS (CAHIERS MAGELLANES-NS, 2024)
This study explores the role of microfinance in enhancing women's entrepreneurial success. It examines how access to microfinance impacts women's ability to start and sustain businesses, focusing on financial and non-financial aspects. The research employs a mixed-methods approach, combining quantitative surveys and qualitative interviews with women entrepreneurs. Findings reveal that microfinance significantly contributes to business growth, profitability, and socio-economic empowerment. However, challenges such as socio-cultural barriers, high-interest rates, and lack of financial literacy persist. The study highlights the importance of tailored microfinance programs and comprehensive support services to maximize the benefits for women entrepreneurs. These insights are crucial for policymakers, microfinance institutions, and stakeholders aiming to promote inclusive economic development.